Pengaruh Kompetensi Intelektual, Kompetensi Emosional, Dan Kompetensi Sosial Terhadap Kinerja Pegawai Di Universitas Pattimura Ambon - Muhammad Bugis; Amin Ramly (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of intellectual competence, emotional competence, and social competence on employee performance at Pattimura University Ambon. The research was motivated by the importance of holistic competency development in improving the quality of employee performance in the university environment, especially in Eastern Indonesia which has unique characteristics. The research method used was quantitative with a survey approach, involving 289 employees as a sample taken by purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of XLSTAT software to test the relationship between variables. The results showed that the three dimensions of competence had a positive and significant effect on employee performance, with the most dominant influence of social competence (coefficient 0.477), followed by intellectual competence (0.313) and emotional competence (0.205). This finding confirms the importance of developing intellectual, emotional and social competencies in an integrated manner to improve employee performance at Pattimura University Ambon. This research recommends strengthening holistic and sustainable HR training and development programs to support the achievement of the university's vision and mission